Electrospun Collagen Nanofiber Membranes for Regenerative Medicine - Nidal Hilal (Nanofiber Membranes for Medical, Environmental, and Energy Applications, 2019)
Population growth has always been and will remain one of the main drivers of water demand, along with a larger amount of wastewater generation. As a result, the need for technological innovation to enable novel water management cannot be overstated. In the past decades, membrane separation technologies have widely been used for desalination and water/wastewater treatment applications. Among them, the membrane distillation (MD) process has recently received much more attention due to its various advantages. However, one of the most important challenges in the way of industrialization of MD process is the lack of novel and specific membranes. Nanotechnology can play a vital role in advancing MD membranes for desalination and water treatment. In this regard, Electrospinning technology for fabricating nanofibrous membranes has emerged as a versatile technique with promising features. This chapter discusses newly developed electrospun nanofibrous membranes for enhancing MD processes for desalination and water/wastewater treatment purposes.